Quality of Life Patients HIV Based on Characteristic, Duration of Diagnosis, and Types Antiretroviral (ARV) - Amelia, Iftikar Salma; Rahayuwati, Laili; Harun, Hasniatisari; Ibrahim, Kusman; Prawesti, Ayu; Pramukti, Iqbal (Poltekkes Kemenkes Tanjung Karang, 2024)
Human Immunodeficiency Virus (HIV) is a retrovirus that attacks the body's immune system, leading to an increase in morbidity and mortality rates in Indonesia. HIV can cause problems in both physical and emotional aspects, impacting the quality of life in daily activities. This study aims to determine the health-related quality of life of HIV patients based on characteristics, duration of diagnosis, and types of antiretroviral treatment at RSUD Sumedang. The research utilized a cross-sectional design with a population of HIV patients visiting the teratai clinic at RSUD Sumedang. Sampling was done using consecutive sampling, involving 71 respondents who met the inclusion criteria. Data analysis in this study utilized univariate analysis and bivariate analysis using chi-square. The univariate analysis results indicated that the majority of respondents had a good quality of life at 56.3%, measured using EQ-5D-5L, with the anxiety/depression domain being the one with the most issues. The results of bivariate analysis using chi-square showed no significant relationship between characteristics, duration of diagnosis, and types of antiretroviral treatment with the quality of life in HIV patients at RSUD Sumedang. It was concluded that the quality of life of HIV patients at RSUD Sumedang, measured using EQ-5D-5L, is mostly good. The domain of anxiety/depression is the most problematic.